2017
DOI: 10.1007/s11999-017-5389-3
|View full text |Cite
|
Sign up to set email alerts
|

Can A Multivariate Model for Survival Estimation in Skeletal Metastases (PATHFx) Be Externally Validated Using Japanese Patients?

Abstract: Level II, prognostic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 13 publications
2
21
0
Order By: Relevance
“…Each has demonstrable prognostic value in estimating survival in patients with advanced cancer [12, 2, 23, 22, 24, 17 -21, 41, 15, 11, 7]. In doing so, we produced models with high discriminatory capacities in an independent cohort, similar to the internal validation statistics reported by Janssen et al [8] as well as the external validation of PATHFX by Forsberg et al [18], Piciolli et al [13] and Ogura et al [37]. This is an important observation, since models exhibit a decrease in discriminative ability when presented with unknown records during external validation.…”
Section: Limitationssupporting
confidence: 54%
See 2 more Smart Citations
“…Each has demonstrable prognostic value in estimating survival in patients with advanced cancer [12, 2, 23, 22, 24, 17 -21, 41, 15, 11, 7]. In doing so, we produced models with high discriminatory capacities in an independent cohort, similar to the internal validation statistics reported by Janssen et al [8] as well as the external validation of PATHFX by Forsberg et al [18], Piciolli et al [13] and Ogura et al [37]. This is an important observation, since models exhibit a decrease in discriminative ability when presented with unknown records during external validation.…”
Section: Limitationssupporting
confidence: 54%
“…Piccioli et al [13] observed similar findings in DCA analysis of the PATHFX 3-month model although they found a threshold at 0.90, which is increased to our findings (0.52). Ogura et al [37] observed something similar for their 1 month (0.80) and 3month prediction model (0.60). This large difference of net benefit across threshold probabilities can be explained by our two cohorts being very homogeneous (most variables have the same distribution in the training and the validation cohorts and no significant difference in survival pattern was observed) in contrast to the training and various validation cohorts of the PATHFx.…”
Section: Limitationsmentioning
confidence: 54%
See 1 more Smart Citation
“…No new patient data was developed or accessed. To externally validate the results, one Western data set including 815 patients (Scandinavia) 5 and one Eastern (Japanese) data set with 261 patients were used 8 . Both data sets were used to validate the first‐generation PathFx models and have been described in detail (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…The tool was then externally validated in Scandinavian 5 and Italian 6 patients. The models were then expanded to predict 1‐ and 6‐month survival, 7 which were, in turn, externally validated in Japanese patients 8 . Finally, 18‐ and 24‐month models were added to provide a comprehensive survival profile.…”
Section: Introductionmentioning
confidence: 99%